Asbestos-related diseases in entertainment workers / Patologie asbesto-correlate in lavoratori dello spettacolo - Mensi, C.; Gerberi, A.; Bordini et al., L. (La Medicina del Lavoro, 2010)
Objectives: To investigate asbestos exposure in 4 patients (3 cases of malignant mesothelioma and 1 case of pleural plaques) previously employed in the entertainment business. Methods: The patients were seen at the Occupational Health Unit of the “Clinica del Lavoro Luigi Devoto” in Milan (Italy). Information regarding exposure to asbestos (occupational, environmental, and familial) was collected through a standardized questionnaire administered to the patients by an occupational physician. Results and conclusion: The presence of asbestos in the building structures and its use were described by all patients. The presence of asbestos in public buildings used for entertainment such as cinemas and theatres was in fact confirmed by the Occupational Health Services of the Local Heath Unit. An occupational aetiology was recognised in all the cases mentioned above, thus leading to the identification of an atypical occupational sector at risk in the past for asbestos exposure.Patologie asbesto-correlate in lavoratori dello spettacoloObiettivi: verificare l’esposizione ad amianto in 4 pazienti (3 casi di mesotelioma maligno ed 1 di placche pleuriche) che avevano lavorato nel pubblico spettacolo. Metodi: I pazienti erano afferenti all’Unità Operativa di Medicina del Lavoro della “Clinica del Lavoro Luigi Devoto” di Milano (Italia). Informazioni inerenti l’eventuale esposizione ad amianto (occupazionale, ambientale o familiare) sono state raccolte attraverso un questionario standardizzato somministrato ai pazienti da medici del lavoro. Risultati e conclusioni: La presenza e l’utilizzo di amianto nell’ambiente di lavoro è stata descritta da tutti e 4 i casi ed è stata confermata dai Servizi PSAL. Per tutti questi casi si è posta diagnosi di malattia professionale avviando le pratiche per il riconoscimento assicurativo.